Integrative immunology identified interferome signatures in uveitis and systemic disease-associated uveitis - Munhoz, Danielle Dias; Fonseca, Dennyson Leandro M.; Filgueiras, Igor Salerno; Dias, Haroldo Dutra; Nakaya, Helder I.; Jurisica, Igor; Ochs, Hans D.; Schimke, Lena F.; Rizzo, Luiz Vicente; Cabral-Marques, Otavio (Frontiers in Immunology, 2025)
IntroductionUveitis accounts for up to 25% of global legal blindness and involves intraocular inflammation, classifed as infectious or non-infectious. Its complex pathophysiology includes dysregulated cytokines, particularly interferons (IFNs). However, the global signature of type I, II, and III interferon-regulated genes (Interferome) remains largely uncharacterized in uveitis.MethodsIn this study, we conducted an integrative systems biology analysis of blood transcriptome data from 169 non-infectious uveitis patients (56 isolated uveitis, 113 systemic disease-associated uveitis) and 82 healthy controls.ResultsModular co-expression analysis identified distinct cytokine signaling networks, emphasizing interleukin and interferon pathways. A meta-analysis revealed 110 differentially expressed genes (metaDEGs) in isolated uveitis and 91 in systemic disease-associated uveitis, predominantly linked to immune responses. The Interferome database confirmed a predominance of type I and II IFN signatures in both groups. Pathway enrichment analysis highlighted inflammatory responses, including cytokine production (IL-8, IL1-β, IFN-γ, β, and α) and toll-like receptor signaling (TLR4, TLR7, TLR8, CD180). Principal component analysis emphasized the IFN signature’s discriminative power, particularly in systemic disease-associated uveitis. Machine learning identified IFN-associated genes as robust predictors, while linear discriminant analysis pinpointed CCR2, CD180, GAPT, and PTGS2 as key risk factors in isolated uveitis and CA1, SIAH2, and PGS in systemic disease-associated uveitis.ConclusionThese findings highlight IFN-driven imune dysregulation and potential molecular targets for precision therapies in uveitis.